Coaxial Self-Trapping of White and Gray Regions of an Incandescent Field: A Bright Core with a Dark Cladding. (9th September 2012) - Kasala, Kailash; Saravanamuttu, Kalaichelvi
Abstract : We report the generation of a self-trapped incoherent hybrid beam comprising a dark-sheathed bright core. The hybrid beam originates from refractive index changes in a photocrosslinkable organosiloxane, which allow simultaneous and cooperative self-trapping of a gray ring with a white core embedded in a broad incandescent beam. The core narrowed and increased in intensity while the encircling gray ring decreased in intensity until rendered very dark. This dark sheath improves light confinement in the bright core and protects it from interactions with nearby self-trapped filaments. This is the first example of a self-trapped hybrid beam, which is moreover spatially and temporally incoherent.